Bryum billardieri Schwaegr. against EV71 infection: in vitro and in vivo antiviral effects, identification of molecular mechanisms and active monomers - Wang, Yun-Yu; Li, Qian; Han, Xiu-Wei; Wan, Xin-Huan; Zhang, Li; Niu, Feng-Jv; Xin, Yi-Zhou; Zhou, Chang-Zheng (Frontiers in Pharmacology, 2023)
Enterovirus 71 (EV71) commonly causes symptoms such as hand, foot, and mouth disease (HFMD) in infants and children and may lead to neurological disease and even death in severe cases. Appropriate vaccines for the prevention of HFMD are available in the clinic; however, they present different and serious adverse effects that cannot guarantee compliance and efficacy. The purpose of this study was to analyze the potential mechanism of Bryum billardieri Schwaegr. (BBS) against EV71 and analyze its potential active components. A previous in vitro antiviral assay was used to determine the best extraction method for the active site of BBS against EV71, and the results showed that the antiviral activity of BBS was more pronounced in the fraction that was extracted by aqueous extraction and alcoholic precipitation and then obtained by purification on a silica gel column (dichloromethane:methanol = 0:100). In addition, the therapeutic effects of BBS on EV71-infected mice were further investigated by in vivo pharmacological experiments. BBS reduced the lung index, viral titer, and degree of EV71-induced lung, brain, and skeletal muscle damage. The mechanism of anti-EV71 activity of BBS was also investigated by using ELISA and qRT-PCR, and it was found that BBS exerted its action mainly by regulating the expression of TLR3, TLR4, TNF-α, IL-2, and IFN-γ by modulating the activation of NF-κB and JAK2/STAT1 signaling pathways. Finally, the chemical structures of the active monomers in BBS were determined by using UPLC-MS and NMR techniques. The study revealed that one of the monomers on which BBS exerts its antiviral activity is saponarin. In conclusion, the results of this study suggest that BBS is considered a natural anti-EV71 product with enormous potential, and saponarin would be its non-negligible active monomer.